Categoriality as a form of expressiveness: expressive speech in Tatar and French - Rauchania R. Mingazova, Alsu F. Valeeva, Albina K. Gizatullina (Opción, 2019)
The purpose of this research is to compare expressive sentences in Tatar and French. Linguistic methods and techniques (comparative-typological, universal-differential and descriptive) were applied to analyze the actual material in accordance with the research goal and objectives. As a result, confidence and readiness to defend one’s position are the reason for making many speech genres (ordering, stating, reproaching, etc.) more expressive. As a conclusion, this research revealed similar typological features indicating a certain similarity of the Tatar and French languages belonging to different language families.